Faktor-Faktor Faktor-Faktor Yang Mempengaruhi Transfer Pricing Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia - Marbun, Yulia; Fitriana, Nur (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The aim of this research is to prove empirically whether transfer pricing is influenced by tax variables, bonus mechanism, and probability in mining companieslisted on the Indonesia stock exchange. This research is a quantitative research with sampling using the purposive sampling method. The data collection from 12 companies being a sample of mining companies listed on the Indonesia stock exchange in 2019-2023. This research uses multiple linier regression analysis tecniques with research data processing testing using spss 22. The research results show that the tax variabel have an effect on transfer pricing, the bonus mechanism do not effect on transfer pricing, and profitability does not effect on transfer pricing.